Impact of Acute Insulin Resistance on Myocardial Blush in Non-Diabetic Patients Undergoing Primary Percutaneous Coronary Intervention - Kasem, Soheir M.; Saied, Ghada Mohamed; Hegazy, Abdel Nasser MA; Abdelsabour, Mahmoud (Frontiers in Cardiovascular Medicine, 2021)
Background: Myocardial blush grading is considered to be a valuable tool for assessing coronary microvasculature and myocardial perfusion in patients undergoing coronary angiography and angioplasty and its reduction identifies patients at high risk. This study aimed to investigate the association between acute insulin resistance and myocardial blush in non-diabetic patients with ST-segment elevation myocardial infarction (STEMI). Methods: A total of 240 non-diabetic patients with STEMI who underwent primary percutaneous coronary intervention were consecutively enrolled. Relationship of homeostasis model assessment –estimated insulin resistance (HOMA-IR) to myocardial blush and in-hospital outcome were investigated. Results: Higher HOMA-IR tertile was observed in obese patients, with hyperinsulinemia, had Killip class >1, with higher CPK-MB level and was correlated to impaired myocardial blush after adjusting for the other confounding risk factors. It was also concluded that higher HOMA-IR was independently associated with no/minimal myocardial blush after STEMI. Moreover, it was found to be an independent predictor of in-hospital mortality, pulmonary edema and impaired left ventricular systolic function. Conclusion: This study revealed that acute insulin resistance was prevalent in non-diabetic patients with STEMI and was an independent predictor for post-infarction myocardial and microvascular injury and poor in-hospital outcome.